Tree structure of the secondary forest at the Pindo Mirador Biological Station, Pastaza, Ecuador - Paredes Ulloa, Christopher O.; niversidad de Pinar del Río, calle Martí final, ciudad de Pinar del Río (2020)
The evergreen piedmont forests of the Biological Station Pindo Mirador, province of Pastaza, Ecuador, have been poorly studied, proposing with the research, to characterize the tree structure of the secondary piedmont evergreen forest in a sector of the forest area of the Station, providing information for the protection actions that are developed. Four plots of 0,1 ha were established covering a sampling area of 0,4 ha; all trees with D1.30 from the soil ≥ 10 cm were measured, determining their absolute height, and four diametric classes and similar number of height ranges were established with the records. Species and plot abundances, diametric classes and height ranges were analyzed to extract their descriptive statistics, and by non-parametric comparisons to establish differences between them. The contribution of species to the forest structure was assessed by determining Structural Diversity Indexes, including the Importance Value Index (IVI) for each. The results show a richness of 49 species belonging to 36 genera of 27 families, where trees with diameters between 10 and 20 cm and heights between 8 and 20 m predominate. It is concluded that it is a heterogeneous forest typical of the Andean-Amazon transition, of low species richness, whose vertical structure of the dominant flight is of the medium floor or subcanopy, medium dense, dominated by the species oblong Hyeronima oblonga and Piptocoma discolor, which have the biggest influence on the forest structure.